1998
DOI: 10.1016/s0022-5347(01)62976-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity: A Biomarker of Cell Proliferation, Not Malignant Transformation

Abstract: Telomerase activity is readily detected in most cancer biopsies, but not in premalignant lesions or in normal tissue samples with a few exceptions that include germ cells and hemopoietic stem cells. Telomerase activity may, therefore, be a useful biomarker for diagnosis of malignancies and a target for inactivation in chemotherapy or gene therapy. These observations have led to the hypothesis that activation of telomerase may be an important step in tumorigenesis. To test this hypothesis, we studied telomerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
13

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 9 publications
4
53
1
13
Order By: Relevance
“…The Ki-S2/ Ki-S5 ratios differed at most fourfold, between 0.2 and 0.8, whereas telomerase levels varied more than 100-fold. Considering the recent suggestion that telomerase activity is not a unique tumor marker but 'only' another marker for cellular proliferation [96], these results indicate that telomerase activity as a prognostic tumor marker has at least a superior diagnostic resolution. In addition to telomere maintenance, the possible involvement of telomerase in DNA repair could make it even more informative in predicting chemoresistance (see below).…”
Section: G Krupp W Klapper and R Parwareschmentioning
confidence: 68%
See 1 more Smart Citation
“…The Ki-S2/ Ki-S5 ratios differed at most fourfold, between 0.2 and 0.8, whereas telomerase levels varied more than 100-fold. Considering the recent suggestion that telomerase activity is not a unique tumor marker but 'only' another marker for cellular proliferation [96], these results indicate that telomerase activity as a prognostic tumor marker has at least a superior diagnostic resolution. In addition to telomere maintenance, the possible involvement of telomerase in DNA repair could make it even more informative in predicting chemoresistance (see below).…”
Section: G Krupp W Klapper and R Parwareschmentioning
confidence: 68%
“…T-lymphocytes from peripheral blood have only low telomerase activity [75][76][77], and some somatic epithelial tissue samples (uroepithelial, breast, prostate) are completely negative [96]. However, telomerase activity drastically increased upon in vitro stimulation of cellular proliferation [77][78][79][80][81]96].…”
Section: Telomerase Activity In Telomerase-competent Cells Is Linked mentioning
confidence: 99%
“…It is entirely possible, nevertheless, that during the years of pterygium development the proliferation activity varies. In another very recent study, increased telomerase activity, which serves as a measure of cell proliferation [4], was observed in two-thirds of the pterygia tested [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies by others have demonstrated that telomerase activity is a biomarker of cell proliferation and cell growth rate. 31 Telomerase activity is repressed in cells that exit the cell cycle and become quiescent. 32 Growth suppression and apoptosis could account for the decrease in telomerase activity after Ad5CMV-p53 transduction ( Table 1).…”
Section: Discussionmentioning
confidence: 99%